Nature Conservation - a Losing Battle - Subramanyam, K.; Sreemadhavan, C. P. (Indian Forester, 1969)
The importance of a rational and prudent approach to the exploitation of natural resources and conservation of biotic communities is stressed. The major problems facing the conservationists are briefly reviewed. They are: (1) Environmental deterioration, principally air, water and soil pollution and (2) the population explosion. The importance of pesticides as a pollutant of soil and water is pointed out and it is suggested that the problem of pest control should be viewed primarily in terms of population ecology. Attention is focussed on the role of rapidly increasing human population in environmental deterioration. The urgent need for the establishment of a powerful governmental agency to deal with the population and environment problems is emphasized.